Clinical effects of pulsed dye laser dynamically combined with triamcinolone acetonide in the treatment of postoperative recurrence keloids - Zhennan Liu; Jiamin Zhang; Xin Guo (Wolters Kluwer Medknow Publications, 2023)
Purpose: This study aimed to explore the clinical effects of pulsed dye laser (PDL) dynamically combined with triamcinolone acetonide (TAC) in the treatment of post-operative keloids recurrence. Materials and Methods: This study retrospectively analysed the clinical data of 29 keloid patients (with 39 keloids) from April 2014 to February 2020. The patients were divided into TAC group (14 patients with 19 keloids) and dynamic treatment group (15 patients with 20 keloids) according to the post-operative treatment that they received. The keloids were assessed by Vancouver scar scale (VSS), patient and observer scar assessment scale (POSAS) and the effect of keloids on the quality of life of patients was evaluated with dermatology life quality index (DLQI) scale before the surgical treatment, at any time of relapse, and 24 months after the surgical treatment. The recurrence-free interval, relative cure time, and the cumulative times of TAC injection when the relative cure could be assessed as achieved, and the incidence of adverse reactions were calculated. Results: Patients experiencing a recurrence within 2 years after surgery included 19 keloids (25.33%) that developed a recurrent event within 6 months, 34 keloids (45.33%) that within 12 months, and 39 keloids (52.00%) that within 24 months after surgery. Anterior chest keloid had the highest recurrence rate and ear keloid had the lowest recurrence rate. The total pigmentation and vascularity (VSS and POSAS) scores of patients' keloids in TAC group and dynamic treatment group 24 months after treatment were significantly lower than those before treatment and at relapse (P < 0.05), the total VSS and POSAS scores were significantly lower at 24 months than before treatment and at relapse (P < 0.05), and the DLQI scale score was significantly lower at 24 months than before treatment (P < 0.05). The VSS and POSAS scores of patients' keloids at 24 months after treatment were significantly lower in the dynamic treatment group than in the TAC group. The relative cure time of patients' keloids in the dynamic treatment group was 6.47 ± 2.72 months, which was significantly shorter than 8.65 ± 3.67 months in the TAC group (P < 0.05). The cumulative number of TAC injections that were given to achieve a relative cure of patients' keloids in dynamic treatment group was 3.60 ± 1.76, which was significantly less than 5.24 ± 2.25 in TAC group. The total incidence of adverse reactions was lower in the dynamic group than in TAC group, but this difference did not reach statistical significance (P > 0.05). Conclusions: Compared with TAC injection alone, PDL dynamically combined with TAC in the treatment of keloid with post-operative recurrence can shorten the relative cure time, reduce the number of TAC injections and improve the clinical efficacy.